Studying a Television Audience in Malaysia: A Practice of Audience Ethnography in Kampung Papitusulem, Sabak Bernam, Selangor - Rofil, Lily El Ferawati (Universiti Putra Malaysia, 2016)
This article discusses the ethnographic nature of audience studies and the practices of audience ethnography in Kampung Papitusulem, Sabak Bernam. Although ethnography has been adopted in the studies of media reception worldwide, it is not a popular methodological tradition among the media and communication researchers in Malaysia. However, considering the multicultural nature of the Malaysian population and media, audience ethnography should be considered as one of the practical methodologies in media and communication research in the country. Based on the empirical ethnographic research involving a group of Malay-Javanese women in Kampung Papitusulem, Sabak Bernam, this article presents the methodological issues of an ethnographic approach in studying Malaysian television audiences. The practice of audience ethnography in the kampung indicates that the methodology would likely be applicable in media audience research in rural Malaysia by considering practical data collection techniques including partial immersion of fieldwork, conversational interviews, and selected participant observation.